Operational numerical wind-wave model for the Black Sea - KORTCHEVA, A.; KORTCHEV, G.; LEFEVRE, J. M. (Mediterranean Marine Science, 2000)
In this paper the discrete spectral shallow water wave model named VAGBUHL1 is presented. This model is used for real-time Black Sea state forecasting. The model was verified against satellite ERS-2 altimeter wave height data.